INVESTIGATING TEACHER LEADERSHIP: FRACTIONS OF TEACHER LIFEWORLD EXPERIENCE - Ponomarenko, Tetiana (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
The phenomenon of teacher leadership has been investigated over the past few decades. The purpose of the current paper is to explore the phenomenon of teacher leadership through investigation of lifeworld experience of Lithuanian in-service teachers in terms of eight lifeworld experience fractions: selfhood, sociality, embodiment, temporality, spatiality, project, discourse and moodedness. The focus group interview method was applied in order to explore the opinions and experiences of teachers. In total, 5 focus group interviews with 12 teachers were conducted. The research results indicate that the fractions of selfhood, moodedness and sociality are the most salient for Lithuanian teachers. The interpersonal nature of teacher leadership, the need of social persuasion and capability to sustain a successful interaction with students are discussed.